2001
DOI: 10.1016/s0029-7844(00)01201-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo-controlled evaluation of intramuscular interferon beta treatment of recurrent human papillomavirus

Abstract: Intramuscular injections of interferon beta were effective for treating recurrent HPV lesions, particularly when associated with CIN. The only side effects were mild and controllable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Approximately 56% of the women with persistent hrHPV infections remained positive after a year of follow-up, and the mean time for clearance of hrHPV infection was close to sixteen months [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 56% of the women with persistent hrHPV infections remained positive after a year of follow-up, and the mean time for clearance of hrHPV infection was close to sixteen months [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-b, like IFN-a, is classified as a type I interferon and can effectively inhibit tumor cell growth by inducing cell differentiation and accumulation of transformed cells in S-phase, thereby effectively inducing failure to progress to G2 and M and promoting apoptosis [ 17 ]. IFN-b, administered either alone or in combination with other agents as intramuscular injections, has been used for more than 10 years to treat HPVs [ 18 ]. In a meta-analysis, Yang et al [ 19 ] reported that, of 1,445 cases of genital warts treated with IFN-b, 27.4% to 44.4% were completely cured; there are also reports that IFN-b is effective in treating CIN-related, recurrent HPV lesions [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-b, administered either alone or in combination with other agents as intramuscular injections, has been used for more than 10 years to treat HPVs [ 18 ]. In a meta-analysis, Yang et al [ 19 ] reported that, of 1,445 cases of genital warts treated with IFN-b, 27.4% to 44.4% were completely cured; there are also reports that IFN-b is effective in treating CIN-related, recurrent HPV lesions [ 18 ]. Studies on the effects of siRNAs and IFN-b in HPV infection-related cancers have not been attempted.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effects of interferon β (type-I interferon) on recurrent HPV infection lesions have been clinically proven, especially in patients with cervical intraepithelial neoplasia (CIN) [306]. Type I IFN strongly induces p56 expression, and p56 binds the E1 protein of several HPV serotypes [307].…”
Section: Viral-specific Nuclear Transport Inhibitorsmentioning
confidence: 99%